Guidelines to operationalize a model to facilitate male involvement in the reproductive health context by the registered nurses - Justus, Amukugo Hans; Hanna, Neshuku; Nangombe, Julia Paula (International Journal of Advanced Nursing Studies, 2015)
The purpose of this article is to describe the guidelines for operationalising a model to facilitate male partner involvement in RH. Guidelines were developed for the implementation of the model to facilitate male partner involvement in RH through the management of a partnership environment. These guidelines may be implemented in those health facilities that provide RH services, namely, clinics, health centres and hospitals. The nurses, in collaboration with significant stakeholders from the community, representatives from the line ministries and NGOs, will be able to facilitate male partner involvement in RH.These guidelines and strategies were derived from the conceptual framework which was generated by means of deductive reasoning and analysis. The guidelines and strategies at each level are aimed at facilitating male partner involvement in RH through the management of the partnership environment by enabling male partners to become actively involved and participate and to eliminate those factors that impede the full participation of male partners in the RH context. The chapter will focus on these guidelines which are expressed in terms of the aims and strategies of each of the four phases in facilitating male partner involvement in RH.